Vulnerability of Reinforced Concrete Columns to External Blast Loading - Al-Bayti, Abdullah (Université d'Ottawa / University of Ottawa, 2017)
Reinforced concrete columns are essential elements that are responsible for overall strength and stability of structures. Loss of a column within a frame can cause progressive collapse. While some research has been conducted on blast performance of reinforced columns, primarily under far-field explosions, very limited work exists on the effects of close-in explosions. Dynamic response of concrete columns, in multi storey building, was investigated under close-in blast loads numerically, using FEM software LS-DYNA. A six-storey reinforced concrete building was selected for this purpose. Different standoff distance/charge mass combinations were used to investigate the failure modes of external building columns. Three different charge masses were used; i) backpack bomb having 22.67 kg (50 lbs) of TNT, ii) compact sedan car bomb with 227 kg (500 lbs) of TNT and iii) sedan car bomb with 454 kg (1000 lbs) of TNT. The explosives were placed at different distances relatively close to the structure, triggering different failure modes. Effects of transverse reinforcement and column location (edge versus corner column) were studied under different combinations of charge weight and standoff distance. Column response under dynamic blast load was identified as either local or global. The results show that the failure mode with backpack bombs located at small standoff distance is either local breaching or concrete scabbing. Direct shear failure occurred at column supports when higher charge masses were detonated at close distances. As the standoff distance increased the response changed from breaching or direct shear to diagonal tension and flexure. The column transverse reinforcement played a major role in controlling diagonal shear cracks and promoting flexural response. Hence, the amount and spacing of transverse reinforcement were observed to be important design parameters.
Keywords: Reinforced Concrete Columns; Close-in Explosions